DETERMINAN PERILAKU LOYALITAS KONSUMEN INDOMARET DI JAKARTA BARAT - Debbie Aryani Tribudhi; Soeharjoto Soekapdjo (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2019)
Purpose of this study is to know about Indomaret customer loyalty behavior at West Jakarta. Structural Equation Models (SEM) methods with value equity , relationship equity , brand equity, positive emotions, negative emotions as a independent variable and loyalty intentions as a dependent variable. Result from 225 sample with purposive sampling technique shown that there are positive and significant influence between brand equity to loyalty intentions, relationship equity to loyalty intentions, and positive emotions to loyalty intentions. There is negative and significant influence from negative emotions to loyalty intentions, but there's no influence between value equity to loyalty intentions. Increasingly competitive business at minimarket sector  and advancement of digital technology,  Indomaret should have an inovation  at lots of area and have cooperation with another related parties to have a loyal customer.